Optimised multi-camera systems for dimensional control in factory environments. (August 2018) - Robson, Stuart; MacDonald, Lindsay; Kyle, Stephen; Boehm, Jan; Shortis, Mark
As part of the United Kingdom's Light Controlled Factory project, University College London aims to develop a large-scale multi-camera system for dimensional control tasks in manufacturing, such as part assembly and tracking. Accuracy requirements in manufacturing are demanding, and improvements in the modelling and analysis of both camera imaging and the measurement environment are essential. A major aspect to improved camera modelling is the use of monochromatic imaging of retro-reflective target points, together with a camera model designed for a particular illumination wavelength. A small-scale system for laboratory testing has been constructed using eight low-cost monochrome cameras with C-mount lenses on a rigid metal framework. Red, green and blue monochromatic light-emitting diode ring illumination has been tested, with a broadband white illumination for comparison. Potentially, accuracy may be further enhanced by the reduction in refraction errors caused by a non-homogeneous factory environment, typically manifest in varying temperatures in the workspace. A refraction modelling tool under development in the parallel European Union LUMINAR project is being used to simulate refraction in order to test methods which may be able to reduce or eliminate this effect in practice.